Detection of prion gene promoter and intron1 indel polymorphisms in Anatolian water buffalo (Bubalus bubalis) - Oztabak, K.; Ozkan, E.; Soysal, I.; Paya, I.; Un, C. (WILEY, 2009)
P>Bovine spongiform encephalopathy (BSE) is a fatal disease caused by miss folded prion protein. Studies in the cattle, comparing genetic data from BSE diseased and healthy animals have shown that indel polymorphisms in the promoter and intron 1 of PRNP gene were associated with disease susceptibility. Several studies were conducted to find out allele and genotypic frequencies of indel polymorphisms in promoter and intron 1 of the cattle PRNP gene. Unlike domestic cattle and bison, no indel polymorphisms of the PRNP promoter and intron 1 were examined in any population of the water buffalo (Bubalus bubalis). Aim of this study was to analyse frequencies of allele, genotype, and haplotype of the indel polymorphisms (23 bp indel in promoter and 12 bp indel in intron 1) in prion protein coding gene (PRNP) of water buffalo. Therefore a PCR based procedure, previously used in cattle to detect indel polymorphisms of PRNP promoter and intron 1 locus, was applied to 106 Anatolian water buffalo DNAs. Our results have revealed high frequency of in variants and in23/in12 haplotype for PRNP promoter and intron 1 indel polymorphisms in water buffalo. The results of the study have demonstrated that frequencies of allele, genotype, and haplotype of the indel polymorphisms in PRNP gene of the Anatolian water buffalo are significantly different those from cattle and bison PRNP indel polymorphisms.
Keywords: indel polymorphisms; PRNP; water buffalo; PROTEIN GENE; POTENTIAL ASSOCIATION; PRNP GENE; US CATTLE; BSE; SUSCEPTIBILITY; POPULATION; GENOTYPES; HOLSTEIN; SCRAPIE; Agriculture